Professional Teacher Governance in Improving the Quality of Education - Anjur Simanullang; Binur Panjaitan (Jurnal Mantik, 2022)
Educational governance is a process of planning, organizing, directing, monitoring, and evaluating education so that it can achieve the educational goals that have been determined effectively and efficiently. Professional teachers will greatly affect the achievement of the quality of education. The purpose of this research is to find out how professional teacher governance can improve the quality of education. The method used in this study is a descriptive qualitative method using a literature review by collecting sources relevant to the topic of discussion or problems. The results of this study found a significant effect of professional teachers with improving the quality of education.